2020
DOI: 10.1007/s10804-020-09366-w
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Parenting and Drinking Outcomes Among College Students: The Moderating Role of Family Income

Abstract: Helicopter parenting, a form of overcontrol defined by intense levels of monitoring and supervision, has been linked to an increase in risky behaviors in emerging adults. However, the context may modify how helicopter parenting operates on adjustment in this population. The current study sought to better understand the contextualizing role of family income on the relations between helicopter parenting and drinking behaviors during college. Undergraduates (N = 171; 49% female; M age = 18.82; 68% White; M family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Except for one study (Xu & Cao, 2019), the rest of the above-mentioned studies all examined the mediating mechanisms in their associations. McGinley and Davis (2020) explored family income and parent gender as moderators in the association between overparenting and drinking behaviors. They reported that overparenting was a risk factor for emerging adults from high-income families but a protective factor for those from low-income families, and that maternal overparenting was more harmful than paternal overparenting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for one study (Xu & Cao, 2019), the rest of the above-mentioned studies all examined the mediating mechanisms in their associations. McGinley and Davis (2020) explored family income and parent gender as moderators in the association between overparenting and drinking behaviors. They reported that overparenting was a risk factor for emerging adults from high-income families but a protective factor for those from low-income families, and that maternal overparenting was more harmful than paternal overparenting.…”
Section: Resultsmentioning
confidence: 99%
“…Because the focus of this review is on the key findings, many nuanced findings were not able to be included and further discussed. This review highlights the findings on gender (e.g., Kouros et al, 2016; Lindell et al, 2017; Rousseau & Scharf, 2015), race and ethnicity (e.g., Cook, 2020; Rote et al, 2020), family socioeconomic status (McGinley & Davis, 2020) and family structure (Buchanan & LeMoyne, 2020b). For example, Love, Cui, Allen et al (2020) reported that the associations between overparenting and female college students’ competence and self-efficacy were much stronger for fathers than for mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These parenting strategies have an impact on the present and future physical, psychological, social, and emotional development of children (Srivastav & Mathur, 2020). An emerging parenting style is called over‐parenting or helicopter parenting (HP), in which parents over‐intervene in their children's lives and provide them with a great deal of assistance in efforts to prevent them from challenges and obstacles (Kömürcü‐Akik & Alsancak‐Akbulut, 2021; LeMoyne & Buchanan, 2011; Leung, Leung, 2021; McGinley & Davis, 2021). Helicopter parents are well‐intentioned and attempt to solve their children's educational‐, social‐, and work‐related difficulties (McGinley, 2018) to make critical decisions for their children to pursue a more fulfilled life (Segrin et al, 2015) and to prevent their children from making mistakes (Carr et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the positive association was stronger among those co-residing with their parents than those living away from home. McGinley and Davis ( 2021 ) examined the associations between overparenting and college students’ drinking behaviors, and found that, in high-income families, overparenting was positively associated with alcohol consumption and drinking to intoxication, whereas in low-income families, overparenting was negatively associated with most of the negative drinking behaviors examined. In other words, the effects of overparenting on college students’ drinking behaviors varied as a function of the economic status of the family.…”
mentioning
confidence: 99%